2019
DOI: 10.1111/1462-2920.14761
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of antibiotic resistance and phenotypes in 29 outer‐membrane protein mutant strains in Aeromonas hydrophila

Abstract: Summary Although many typical outer‐membrane proteins (OMPs) have been well characterized, the biological functions of many OMPs remain largely elusive. In this study, we successfully constructed 29 OMP knockout strains in the pathogen Aeromonas hydrophila, which account for about 50% of all predicted OMPs in this bacterial species. We then further validated the antibiotics' susceptibility characteristics against 20 antimicrobial reagents in these mutants considering several phenotypes. Our results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 70 publications
0
27
1
Order By: Relevance
“…hamp1 and hamp2 encode hepcidin, an antimicrobial peptide highly conserved in vertebrates (Shike et al , 2004). Hepcidin also has roles in iron homeostasis in macrophages and is induced under stress (Li et al , 2019). Thus, it is worth exploring this role further.…”
Section: Discussionmentioning
confidence: 99%
“…hamp1 and hamp2 encode hepcidin, an antimicrobial peptide highly conserved in vertebrates (Shike et al , 2004). Hepcidin also has roles in iron homeostasis in macrophages and is induced under stress (Li et al , 2019). Thus, it is worth exploring this role further.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the MICs of chloramphenicol, aztreonam and nalidixic acid were decreased when the ompA was disrupted in A. baumannii ( Smani et al, 2014 ). Further, in our previous study, we have observed that the MBCs (minimum bactericidal concentrations) of ceftriaxone sodium, apramycin, neomycin sulfate and gentamicin in Δ AHA_2766 were increased more than 4-fold, whereas the MBCs of norfloxacin and chloramphenicol in Δ AHA_4275 were decreased at least 2-fold ( Li et al, 2019 ). Therefore, we have evaluated the antibiotic susceptibility of these both mutants to FZ antibiotic in this study.…”
Section: Discussionmentioning
confidence: 94%
“…The enzymatic activity detection of hexokinase (HK), 6‐phosphofructokinase (PFK), pyruvate kinase (PK), pyruvate dehydrogenase (PDH), α‐ketoglutarate dehydrogenase (α‐KGDH), succinate dehydrogenase (SDH) and malic dehydrogenase (MDH) were measured by PMS (Phenazine methosulfate) method, slightly modified (Li et al , 2019). The visceral organs from three zebrafish were pooled and homogenized in ice‐cold PBS (pH 7.4) were added at a ratio of 1:15 (w/v).…”
Section: Methodsmentioning
confidence: 99%